2008
DOI: 10.1097/psy.0b013e31817bbc77
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and Cortisol Responses to Laboratory Stressors

Abstract: Results suggest that the nature of the relationship between cortisol activation and rumination may be contingent on how rumination is conceptualized and measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
132
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(147 citation statements)
references
References 37 publications
14
132
1
Order By: Relevance
“…As a result, rumination is likely to occur. Consistent with this premise, recent work has demonstrated that laboratory stressors characterized by SET elicit more rumination than those without an evaluative component [17,18]. Therefore, stressful circumstances that disrupt central goals (e.g., SET) may be particularly likely to lead to rumination, and thus prolong the stress response.…”
Section: Rumination: Definition and Elicitorsmentioning
confidence: 75%
See 1 more Smart Citation
“…As a result, rumination is likely to occur. Consistent with this premise, recent work has demonstrated that laboratory stressors characterized by SET elicit more rumination than those without an evaluative component [17,18]. Therefore, stressful circumstances that disrupt central goals (e.g., SET) may be particularly likely to lead to rumination, and thus prolong the stress response.…”
Section: Rumination: Definition and Elicitorsmentioning
confidence: 75%
“…Distinguishing between trait and state measures is important because trait questionnaires have had limited success in predicting individual differences in stressor-specific rumination following challenging laboratory tasks [17,[26][27][28]. The lack of an association between trait and state rumination could arise because certain situations may overwhelm established coping strategies [29].…”
Section: Measurementmentioning
confidence: 99%
“…For example, naturalistic or laboratory-induced rumination and worry over nontraumatic stressors (public speaking, interpersonal transgressions, etc.) have been linked to cortisol release (e.g., ByrdCraven, Geary, Rose, & Ponzi, 2008;Kuehner, Huffziger, & Liebsch, 2009;McCullough, Orsulak, Brandon, & Akers, 2007;Zoccola, Dickerson, & Zaldivar, 2008). This type of psychological stress, if prolonged, may mediate adverse effects on physical health and aging (Brosschot, 2010;Brosschot, Pieper, & Thayer, 2005;McEwen, 2003).…”
mentioning
confidence: 99%
“…Next, the experimenters informed participants that they had to set up the next phase of the study in another room and asked them to sit quietly until they returned in 5 min. This provided participants with an opportunity to ruminate over their speech performance (for a similar approach to assessing rumination, see Gerin, Davidson, Christenfeld, Goyal, & Schwartz, 2006;Zoccola, Dickerson, & Zaldivar, 2008). At the end of this 5-min period, postevent processing was assessed in two ways.…”
mentioning
confidence: 99%